Les bruits de Madrid. Comment le cinéma écoute la ville - Jean-Paul Aubert (Cahiers de Civilisation Espagnole Contemporaine)
This study focuses on the construction of urban soundscape in six Spanish films which action takes place in Madrid : Surcos (1951) of Antonio Nieves Conde, Los Golfos (1959) of Carlos Saura, ¿Qué he hecho yo para merecer esto! (1984) of Pedro Almodóvar, Madrid (1987) of Basilio Martín Patino, El día de la bestia (1995) of Alex de la Iglesia and Barrio (1998) of Fernando León de Aranoa. This paper tries to explore not only the connotative and referential substance of urban sounds, but also its narrative and symbolic functions.